The Evolution and Characteristics of General Education in Taiwan - Chen, Chao-Chen; Hsiang, Hong-Chuan; Chang, Hsiao-Hui; Shih, Po-Kang (The Korean Association of General Education, 2024)
Taiwanese universities have embraced the spirit of general education from Europe and the United States, launching their own general education programs in the 1980s. Through various social and educational transformations, general education has come to play a critical role in Taiwan's higher education system. This paper outlines the evolution, principles, and key characteristics of general education in Taiwan. Additionally, it explores how universities have introduced diverse general education programs to bridge various gaps: between academic disciplines, between academia and societal issues, between passive and active learning, between the digital and physical worlds, and between local knowledge and global perspectives. The paper concludes by highlighting the potential of even larger gaps emerging in the future due to advancements in AI, suggesting that general education must evolve to address these challenges effectively.